Cardiac rehabilitation attendance and outcomes in coronary artery disease patients - Martin, Billie-Jean; Hauer, Trina; Arena, Ross; Austford, Leslie D; Galbraith, P Diane; Lewin, Adriane M; Knudtson, Merril L; Ghali, William A; Stone, James A; Aggarwal, Sandeep G (Circulation (New York, N.Y.), 2012)
Cardiac rehabilitation (CR) is an efficacious yet underused treatment for patients with coronary artery disease. The objective of this study was to determine the association between CR completion and mortality and resource use. We conducted a prospective cohort study of 5886 subjects (20.8% female; mean age, 60.6 years) who had undergone angiography and were referred for CR in Calgary, AB, Canada, between 1996 and 2009. Outcomes of interest included freedom from emergency room visits, hospitalization, and survival in CR completers versus noncompleters, adjusted for clinical covariates, treatment strategy, and coronary anatomy. Hazard ratios for events for CR completers versus noncompleters were also constructed. A propensity model was used to match completers to noncompleters on baseline characteristics, and each outcome was compared between propensity-matched groups. Of the subjects referred for CR, 2900 (49.3%) completed the program, and an additional 554 subjects started but did not complete CR. CR completion was associated with a lower risk of death, with an adjusted hazard ratio of 0.59 (95% confidence interval, 0.49-0.70). CR completion was also associated with a decreased risk of all-cause hospitalization (adjusted hazard ratio, 0.77; 95% confidence interval, 0.71-0.84) and cardiac hospitalization (adjusted hazard ratio, 0.68; 95% confidence interval, 0.55-0.83) but not with emergency room visits. Propensity-matched analysis demonstrated a persistent association between CR completion and reduced mortality. Among those coronary artery disease patients referred, CR completion is associated with improved survival and decreased hospitalization. There is a need to explore reasons for nonattendance and to test interventions to improve attendance after referral.